Contrasting Dependencies of Photosynthetic Capacity on Leaf Nitrogen in Early- and Late-Successional Tropical Montane Tree Species - Ziegler, Camille; Dusenge, Mirindi Eric; Nyirambangutse, Brigitte; Zibera, Etienne; Wallin, Göran; Uddling, Johan (Frontiers in Plant Science, 2020)
Differences in photosynthetic capacity among tree species and tree functional types are currently assumed to be largely driven by variation in leaf nutrient content, particularly nitrogen (N). However, recent studies indicate that leaf N content is often a poor predictor of variation in photosynthetic capacity in tropical trees. In this study, we explored the relative importance of total area-based total leaf N content (Ntot) and within-leaf N allocation to photosynthetic capacity versus light-harvesting in controlling the variation in photosynthetic capacity (i.e. Vcmax, Jmax) among mature trees of 12 species belonging to either early (ES) or late successional (LS) groups growing in a tropical montane rainforest in Rwanda, central Africa. Photosynthetic capacity at a common leaf temperature of 25 ˚C (i.e. maximum rates of Rubisco carboxylation, Vcmax25 and of electron transport, Jmax25) was higher in ES than in LS species (+ 58 % and 68 % for Vcmax25 and Jmax25, respectively). While Ntot did not significantly differ between successional groups, the photosynthetic dependency on Ntot was markedly different. In ES species, Vcmax25 was strongly and positively related to Ntot but this was not the case in LS species. However, there was no significant trade-off between relative leaf N investments in compounds maximizing photosynthetic capacity versus compounds maximizing light harvesting. Both leaf dark respiration at 25 ˚C (+ 33 %) and, more surprisingly, apparent photosynthetic quantum yield (+ 35 %) was higher in ES than in LS species. Our results imply that efforts to quantify carbon fluxes of tropical montane rainforests would be improved if they considered contrasting within-leaf N allocation and photosynthetic Ntot dependencies between species with different successional strategies.